Albania : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2008)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) for Albania. The note analyzes the National Strategy for Development and Integration (NSDI) program, which represents a significant improvement in process over the previous PRSP. The note discusses that the main strengths of the current process are strong government ownership; a broader participatory process that lays the foundation for greater civil society participation in public policy making; an improved poverty diagnosis; and ambitious plans for monitoring the overall effectiveness of Albania's public expenditures.